Increasing student social awareness in Covid-19 prevention through group guidance using a Reality Approach - Fitratul Ilmi Fajri; Firman Firman (International Journal of Applied Counseling and Social Sciences, 2021)
Today's students have a sense of caring low social to spread of Covid-19 which is indicated by increasing increase case positive and the emergence of various new variants, including the delta, and omicron variants.Social care is the ability of individuals to be responsible for themselvesand peopleotheras well ashaveflavorempathy,sensitiveandresponsivetopersonother.One way that can be done to increasestudent 's social care is to provide group guidance services using the approach I'm on a pedestalreality. The aims of this research are analyze the difference in adolescent social care in preventing Covid-19 the experimental group who was given group guidance services using a reality counseling approach with the control group who was given group guidance services without special treatment.The research method used is quantitative research. This type of research is a quasi-experimental design.Population in study as many as 210 students , with use formula Slovin to 72 students , next from overall data result taken 26 students divided _ become 13 students for group experimenter and 13 students for group control. The sampling used is simple random sampling. Statistical analysis of the data used in this study is nonparametric statistics.The data were analyzed using the Wilcoxon Signed Ranks Test and the Kolmogorov-Smirnov Two Independent Samples with the help of SPSS version 20.The results of the study show that there are differences in social care of the experimental group who are given group guidance services using a counseling approach the reality with the control group being given group guidance services about social care without special treatment